2019
DOI: 10.3389/fimmu.2019.02280
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris lumbricoides Cystatin Prevents Development of Allergic Airway Inflammation in a Mouse Model

Abstract: Severe helminth infections are negatively associated to allergic diseases like asthma; therefore, the immunomodulatory properties of parasite-derived components have been analyzed, raising the possibility of their use as anti-inflammatory molecules. We evaluated the immunomodulatory properties of Ascaris lumbricoides recombinant cysteine protease inhibitor (rAl-CPI) in a mouse model of allergic airway inflammation induced by the house dust mite (HDM) Blomia tropicalis and its effects on human monocyte-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 80 publications
1
32
0
Order By: Relevance
“…Fibrinogen is the acute phase protein whose concentration increases during inflammation. Also, fibrinogen synthesis is increased under the action of interleukin-6 [26,27]. In our studies, animals treated with CRD showed elevated fibrinogen levels that completely corresponded to those reported in the literature.…”
Section: Fig 1 the Influence Of Cholesterol-rich Diet (Crd) On Levesupporting
confidence: 90%
“…Fibrinogen is the acute phase protein whose concentration increases during inflammation. Also, fibrinogen synthesis is increased under the action of interleukin-6 [26,27]. In our studies, animals treated with CRD showed elevated fibrinogen levels that completely corresponded to those reported in the literature.…”
Section: Fig 1 the Influence Of Cholesterol-rich Diet (Crd) On Levesupporting
confidence: 90%
“…Cystatin from N. brasiliensis (NbCys) dampened OVA-specific splenocyte proliferation, as well as IgE and cytokine production by inhibiting cathepsins L and B (89). Similar effects were observed for cystatin (rAl-CPI) from A. lumbricoides, which decreased T H 2 cytokine and IgE production in a mouse model of HDM-induced AAI (92).…”
Section: Immunomodulation Of Asthma and Allergic Diseases By Helminthmentioning
confidence: 67%
“…Mammalian cysteine proteases are required for proteolytic processing of antigens, enabling presentation on MHC class II molecules and effective T cell responses. Cystatins from A. viteae, Brugia malayi, N. brasiliensis, Onchocerca volvulus, Clonorchis sinensis, A. lumbricoides, H. polygyrus, and Litomosoides sigmodontis have been shown to interfere with this process to evade antigen-induced immunity (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94). AvCystatin from A. viteae mitigated airway inflammation and colitis in mice through the induction of IL-10-producing macrophages (93) and reduced pollen-specific responses in lymphocytes from allergic patients (94).…”
Section: Immunomodulation Of Asthma and Allergic Diseases By Helminthmentioning
confidence: 99%
“…Likewise, it was shown that they lead to a weaker antigen-specific antibody response as an untreated control (30). In a mouse model displaying allergic airway inflammation responding to house dust mite, it was shown that CPI from Ascaris lumbricoides (AlCPI), one of the most common parasitic worms found in humans, especially affects perivascular infiltrating cells, eosinophils, neutrophils and goblet cells in the lung and reduces Th2 cytokines (31). Also, a distinct shift from IgE antibodies to IgG, mostly IgG2a, was reported.…”
Section: Helminth-derived Cysteine Protease Inhibitors Affect Antigenmentioning
confidence: 99%